Project culture using Agile project management in hand with traditional project management - Sigurjón Páll Kolbeins 1965- (2013)
The Agile “revolution” within software development projects is changing how we do project management. This paper looks at the project management culture in one of the big three commercial banks in Iceland and how it has evolved the past 6 years. How stakeholders perceive project management through the lenses of those who sponsor projects, supply resources to projects, manage the projects and deliver the projects. The paper takes a look at how Agile project management has changed the culture within the Bank’s IT towards software project management in general and what affect it has had on the traditional project management. Agile „byltingin“ innan hugbúnaðarþróunarverkefna stuðlar að breyttum aðferðum við stýringu verkefna. Ritgerðarrannsóknin skoðar menningu verkefnastjórnunar hjá einum af stærsta banka landsins og hvernig hún hefur þróast síðustu 6 árin. Lýsir hvernig hagsmunaaðilar skynja verkefnastjórnun eða þá sem fjármagna verkefni, leggja til aðföng, stýra verkefni og vinna verkefni. Ritgerðin skoðar hvernig Agile verkefnastjórnun hefur - breytt menningu upplýsingtæknisviðs bankans gagnvart verkefnastjórnun í hugbúðanarþróun og hvaða áhrif það hefur haft á hefðbundna verkefnastjórnun.